Do Master Narratives Change Among High School Students? A Characterization of How National History Is Represented - Carretero Rodriguez, Mario (2014)
Master narratives frame students’ historical knowledge, possibly hindering access to more historical representations. A detailed analysis of students’ historical narratives about the origins of their own nation is presented in terms of four master narrative characteristics related to the historical subject, national identification, the main theme and the nation concept. The narratives of Argentine 8th and 11th graders were analyzed to establish whether a change toward a more complex historical account occurred. The results show that the past is mostly understood in master narrative terms but in the 11th grade narratives demonstrate a more historical understanding. Only identification appears to be fairly constant across years of history learning. The results suggest that in history education first aiming at a constructivist concept of nation and then using the concept to reflect on the national historical subject and events in the narrative might help produce historical understanding of a national past.